Eksplorasi Pengalaman Pegawai Tentang Kepemimpinan, Motivasi Kerja dan Etos Kerja di Dinas Kependudukan dan Pencatatan Sipil Kota Lubuklinggau - Rilda Purnama Sari Gulo; Surajiyo Surajiyo; Yuli Eprianti; Nasruddin Nasruddin (Indo Publishing, 2026)
This study aims to explore employees’ experiences in understanding leadership, work motivation, and work ethic at the Department of Population and Civil Registration of Lubuklinggau City. A qualitative approach with a descriptive exploratory method was employed to gain an in-depth understanding of employees’ subjective experiences in the public service context. Informants were purposively selected, consisting of leaders and employees directly involved in population administration services. Data were collected through in-depth interviews, observation, and documentation, and analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that leadership is perceived as providing direction, role modeling, and work support. Work motivation is shaped by intrinsic and extrinsic factors such as responsibility, recognition, and a supportive work environment. Employees’ work ethic is reflected in discipline, responsibility, and commitment to public service, although variations remain among employees. The study concludes that employees’ experiences of leadership and work motivation play an important role in shaping work ethic within the organization.